Developing Creativity and Early Childhood Creation Through Exploration Activities - selly charmila (Universitas muhammadiyah Banjarmasin, 2022)
Exploration is an activity that children do to something. Exploration activities carried out are to introduce and familiarize children with the natural surroundings. The purpose of Exploration activities in kindergarten is to learn to elaborate and use simple analytical skills in recognizing an object. The research method uses literature study with a qualitative descriptive approach to produce concepts and opinions from in-depth analysis through data collection, data reduction, data presentation and conclusions comprehensively. Children want to observe objects carefully, each unique part, and get to know the way of life or how the object works. One example of creativity development activities in AUD is through exploration activities with various soap bubbles, collecting sized stones and playing with sand